The Politicization of Religion in Indonesia’s 2024 Electoral Cycle: Religious Identity, Elite Mobilization, and Democratic Polarization - Zahrotul Faridah (Al Hikmah, 2026)
Indonesia’s 2024 electoral cycle demonstrated that religion remains an influential resource in democratic contestation. This study examines the politicization of religion through three interconnected dimensions: the deployment of religious identity, the mobilization of religious elites, and the production of democratic polarization. The study employed qualitative library research by analyzing academic literature, election-related documents, media reports, and public discourse concerning the pre-election, campaign, voting, and post-election phases of Indonesia’s 2024 national election. The findings show that religious identity was used to construct moral legitimacy and distinguish political in-groups from out-groups. Religious leaders, communities, and symbols were also mobilized to strengthen electoral credibility and voter loyalty, while digital media accelerated the circulation of religiously framed political narratives. In several cases, Islamic symbols were commodified as electoral assets, shifting public attention from substantive issues such as welfare, inequality, and policy accountability toward symbolic identity competition. However, the presence of religion in politics should not automatically be understood as politicization. The distinction lies between ethical religious participation that contributes moral criticism to public life and the instrumental use of religion for short-term electoral advantage. This study argues that the politicization of religion weakens substantive democracy when it reduces political competition to identity-based loyalty, limits rational deliberation, and deepens social division. The article contributes to religious studies by explaining religion as a contested social and political resource within contemporary Indonesian democracy.